Pengaruh Kedisplinan Dan Minat Belajar Mahasiswa Terhadap Pembelajaran Daring Di STABN Raden Wijaya - Iyut Selviyanti (JURNAL BAHUSACCA, 2021)
Every student is required to behave in accordance with the rules and regulations that apply both in online learning and in everyday life. In addition, having an interest will make students concentrate and enthusiastic in learning. The aims of this research are: (1) to determine and to examine the effect of discipline in online learning, (2) to determine and to examine the student interest in online learning, and to determine and (3) to examine the effect of discipline and student’s interest in online learning. The research was quantitative methods with multiple regression research. The research populations were all of students in STABN Raden Wijaya, while the samples were 49 students of the second term, fourth term, and sixth term on Pendidikan Keagamaan Buddha Study Program. The data collection techniques were through questionnaires, observations, and interviews. The results of this study showed that based on assessment and data analysis the regression equation constant is 2.768, it’s meaning that if the discipline and interest in learning is 0, so the value of online learning is 2.768. The regression coefficient of disciplinary variable is 0.577. So there is discipline influence in online learning. The regression coefficient of learning interest variable is 0.060. So there is no effect of learning interest in online learning. The magnitude of R Square is 0.731. Its means that the variables of discipline and learning interest simultaneously effect on online learning variable in the mount of 73.1%.